Growth of Hydrogenophaga pseudoflava on syngas: design of gas and liquid medium composition based on elemental yield coefficients - Miserez, Florian; Panke, Sven; Zinn, Manfred (Frontiers in Bioengineering and Biotechnology, 2026)
Syngas, an industrial byproduct composed of H2, CO, and CO2, represents an energy-rich substrate for sustainable bioprocesses. However, the toxicity of CO limits its biological utilization to a small number of microorganisms, primarily cultured under anaerobic conditions. To expand the applicability of syngas in aerobic systems, this study investigates the use of Hydrogenophaga pseudoflava as a CO-oxidizing strain capable of converting CO into CO2. This strain has been reported to be a suitable host strain for the engineered biosynthesis of value-added compounds such as the C15 sesquiterpene. The amount of product synthesized depends directly on the amount of CO converted to CO2 and subsequently assimilated as a carbon source. Under previously reported culture conditions, only low CO2 production rates were achieved. To enhance CO oxidation and CO2 generation as a performance indicator, both the gas feed composition and the culture medium were optimized, leading to a 75% increase in specific growth rate (0.072 h-1) and a 380% increase in biomass concentration (11 g L−1). These improvements resulted in a twofold increase in volumetric CO2 production rate. Altogether, our findings establish H. pseudoflava as a promising platform organism for sustainable syngas bioprocesses and provide a base for further metabolic and process engineering toward bioplastic or biofuel production being part of a circular economy.